GLANDULAR HYPERPLASIA OF ENDOMETRIUM. DIAGNOSTIC, CLINIC, TREATMENT - V. A. Pushkarev; G. T. Mustafina; Sh. M. Khusnutdinov; E. V. Kulavskiy; I. M. Mazitov; E. K. Golov; А. V. Pushkarev (Креативная хирургия и онкология, 2017)
The results of examination and treatment of 105 patients with glandular hyperplasia of the endometrium, have done.  The age of women ranged from  24 to 55 years, the average was equal to 42.3 +3.1 years ; reproductive age was 61 patients, 44 menopausal period. The diagnosis of glandular endometrial hyperplasia (ZHE) is set on the basis of ultrasound TVUZI, hysteroscopy, morphological study scraping the uterine mucosa. All patients carried hormone therapy for 6 months: estrogenprogestin, antiestrogen , progestin, progestogens. Efficacy in patients of reproductive age was observed in 43 (70.5  %)  patients, in patients with perimenopausal in 30 ( 68.2 %) coses.In 34,8% patients relapse  glandular hyperplasia of the  endometrium (for  the  period from  1 to 3 years).  Transcervical electrosurgical resection ( ablation) of the  endometrium were  performed. The results  showed the  effectiveness of  endometrial ablation surgery in 90.6% of  patients. Thus,  in the  absence of  therapeutic effect of  hormone therapy, recurrent  uterine  bleeding   and   endometrial  hyperplasia, glandular,  has  hysteroscopic resection surgery (ablation) of the endometrium the high efficacy.